Implementasi Model Project Based Learning dalam Meningkatkan Kreativitas Peserta Didik Kejar Paket A di PKBM Kak Seto Surabaya - Sari, Indah Ayu Permata; Widodo, Widodo (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
The friday class program applies project-based learning which is considered effective in increasing creativity and creating a fun learning environment. This research aims to describe and analyze the implementation of the project-based learning model in increasing the creativity of students equivalent education package A in the Friday class program at PKBM Kak Seto Surabaya. The method used is descriptive qualitative, through data collection techniques of participatory observation, in-depth interviews and documentation. This research uses data analysis in the form of data collection, data reduction, data presentation, and conclusions. The research results show that the implementation of the project-based learning model using a structured project starts from determining the project, planning the steps, preparing the implementation schedule, completing the project, preparing reports and presenting the results, finally evaluating the process and results. Thus, we can see an increase in the creativity of students pursuing package A from their work and participation which is achieved through efforts to provide various projects, provide freedom to explore, and create a conducive learning environment through the use of standardized facilities and infrastructure.